The Need for Core Outcome Reporting in Autologous Fat Grafting for Breast Reconstruction. Issue 5 (November 2016) - Agha, Riaz A.; Fowler, Alexander J.; Pidgeon, Thomas E.; Wellstead, Georgina; Orgill, Dennis P.
Abstract : Introduction: There is growing interest in autologous fat grafting (AFG) for breast reconstruction. This systematic review examines the range of outcomes used across studies of AFG, their definitions and whether there is a need for a core outcome set to aid reporting. Methods: Following the protocol of our systematic review, a search of 20 databases (1986 to March 2014) returned 35 studies which met the inclusion criteria. These were assessed independently by two authors. Disagreements were resolved by consensus. Results: Of the 35 studies, 27 (77%) were case series, 5 (14.3%) were cohort studies, and 3 (8.6%) were case reports. A total of 51 different outcomes were reported. These studies each reported a median of five separate outcomes (range, 2–14), of which a median of 3 outcomes were defined (range, 0–14). A median of 2 outcomes per paper were prespecified in the study methods (range, 0–12) and a median of only 2 outcomes per paper (range, 0–12) were both defined and prespecified. The most commonly reported outcome in studies of AFG was that of "operative details, " reported by 26 studies, and eight different outcome definitions were used. "Cancer recurrence" was reported by 20 studies, with the use of 10 different outcome definitions. Overall, there was a poor proportion of defined and prespecified outcomes that employed a wide range of different outcome definitions. In addition only 14/35 studies stated the number of patients lost to follow-up. Conclusions: There is a need for a core outcomes set for AFG to the breast to minimise outcome and reporting bias and aid evidence synthesis. Our future research will focus in this direction, titled VOGUE orV alidO utcomes for theG rafting of AU tologous Fat to the BrE ast study. We invite all those interested to get in touch with the lead author.